Salvage Surgery for Recurrence after Radiotherapy for Squamous Cell Carcinoma of the Head and Neck. (June 2019) - Elbers, Joris B. W.; Al-Mamgani, Abrahim; van den Brekel, Michiel W. M.; Jóźwiak, Katarzyna; de Boer, J. P.; Lohuis, Peter J. F. M.; Willems, Stefan M.; Verheij, Marcel; Zuur, Charlotte L.
Objective: Most studies that report on salvage surgery after primary radiotherapy for head and neck squamous cell carcinoma (HNSCC) are small and heterogeneous. Subsequently, some relevant questions remain unanswered. We specifically focused on (1) difference in prognosis per tumor subsite, corrected for disease stage, and (2) differences in prognosis after salvage surgery for local, regional, and locoregional recurrences. Study Design: Retrospective analysis. Setting: Single-center study (2000-2016). Subjects and Methods: Patients treated with salvage surgery for HNSCC recurrence after (chemo)radiotherapy. Results: In total, 189 patients were included. Five-year overall survival (OS) was 33%, and median OS was 18 (95% confidence interval [CI], 11-26) months. Treatment-related mortality was 2%. Larynx carcinoma was associated with more favorable local (adjusted hazard ratio [HR] = 4.02; 95% CI, 1.46-11.10; P = .007) and locoregional control (adjusted HR = 5.34; 95% CI, 1.83-15.61; P = .002) than pharyngeal carcinoma. American Society of Anesthesiologists (ASA) score (≥3 vs 1-2: adjusted HR = 3.04; 95% CI, 1.17-7.91; P = .023), pT stage (3-4 vs 1-2: adjusted HR = 4.41; 95% CI, 1.65-11.82; P = .003), and salvage surgery for locoregional recurrences (locoregional vs local: adjusted HR = 3.81; 95% CI, 1.13-11.82; P = .021) were independent predictors for disease-free survival (DFS). Conclusion: Salvage surgery for larynx carcinoma, regardless of disease stage and other prognostic factors, results in more favorable loco(regional) control but not favorable DFS than pharyngeal carcinoma. The observed difference in DFS between salvage surgery for local and regional recurrences was not significant after correction for confounders. However, survival following salvage surgery for locoregional disease is significantly worse. For this subgroup, we propose to consider T status and comorbidity for clinical decision making, as high pT stage and ASA score are independent predictors for worse DFS.